Childhood adversity predicts persistence of suicidal thoughts differently in females and males at clinical high‐risk patients of psychosis. Results of the EPOS project. Issue 4 (23rd July 2018) - Salokangas, Raimo K. R.; Patterson, Paul; Hietala, Jarmo; Heinimaa, Markus; From, Tiina; Ilonen, Tuula; von Reventlow, Heinrich Graf; Schultze‐Lutter, Frauke; Juckel, Georg; Linszen, Don; Dingemans, Peter; Birchwood, Max; et al.
Abstract : Aim: Depression and suicidal ideation (SUI) and behaviour are more prevalent in females than males, and common in clinical high‐risk (CHR) patients. Childhood adversities and trauma (CAT) are associated with adult depression and SUI. The role of gender as a moderator and depression as a mediator for the effect of CAT on SUI has not been explored in CHR patients. Methods: In all, 245 young help‐seeking CHR patients were assessed for SUI (thoughts of killing themselves) with the Beck Depression Inventory at baseline, 9‐month and 18‐month follow‐ups. At baseline, clinical depression was assessed by the Structured Clinical Interview for DSM‐IV (SCID‐I), and CAT by the Trauma and Distress Scale (TADS) which includes the five domains of emotional, physical and sexual abuse, emotional and physical neglect. Results: CAT total and all domains except physical neglect predicted SUI over the study period. The effect of CAT on SUI was mediated via clinical depression and concurrent depression symptoms differently for females and males. In females, the effect of emotional abuse and neglect on SUI was mediated via baseline depression. In males, emotional and physical abuse had a direct effect on SUI, and the effect of sexual abuse and emotional neglect was partly mediated via concurrent depression symptoms. Conclusions: For CHR females, the effect of CAT on adult SUI is mediated via depression, while for males, CAT and its domains have mainly direct effects in maintaining SUI. These gender differences should be taken into account when treating CHR patients with SUI.